Measurement of NMR flow propagators and local numerical analysis of dual scale porous media - Zheng, Yong; Shikhov, Igor; d'Eurydice, Marcel N.; Arns, Christoph (Diffusion Fundamentals, 2017)
Flow propagators have been frequently used in characterisation of porous media and the study of fluid transport behaviour. Previous work considered the shape of measured flow propagators using Nuclear Magnetic Resonance (NMR) discussed the influence of pore geometry, dispersion, relaxation and internal gradients. In addition, numerically simulated flow propagators were also reported. However, a uantitative numerical analysis of local contributions to flow propagators has not been considered in the literature, yet may provide significant new insights into the flow behaviour through complex porous media. In this work we use two types of beads to realize a dual-scale bead pack consisting of micro- and macropore regions for the NMR experiments. A low-field NMR system (2 MHz) was used to measure flow propagators for this sample. We further generated a dual-scale Gaussian Random Field (GRF) image based on porosity, beads diameters and volume fraction of each type of bead for numerical simulations. A Lattice Boltzmann Method (LBM) and Random Walk (RW) technique were combined to derive the simulated flow propagators and validated against experiments. We carry out a local analysis of the flow propagators showing a significant difference in bandwidth of displacements in micro- and macro-pore regions. In addition, the local flow propagators indicate a linear relationship between mixing (the fluid exchange on regions' boundaries) and flow velocities as well as a non-linear correlation between mixing and evolution times.